A template-free synthesis via alkaline route for Nb2O5/carbon nanotubes composite as pseudo-capacitor material with high-rate performance. (1st May 2017) - Luo, Guoming; Li, Heshun; Zhang, Daquan; Gao, Lixin; Lin, Tong
Graphical abstract: Highlights: A simple four-step method to prepare T-Nb2 O5 /CNTs composite. The composite is with well-dispersed CNTs in the Nb2 O5 phase. The composite has excellent large-current discharge property. The composite has a high energy storage property at high current density. Abstract: In this paper, we report a facile template-free method to prepare the T-Nb2 O5 /CNTs composite. The addition of ammonia induces the electrostatic interaction between functionalized CNTs and niobic acid colloids during hydrothermal process, resulting in CNTs homogeneously distributed in the T-Nb2 O5 phase. The obtained T-Nb2 O5 /CNTs composite shows high rate Li + storage ability with typical intercalation capacitive behaviour. The presence of well-dispersed CNTs in Nb2 O5 can apparently reduce the limitation from diffusion process and increase the high rate charge-discharge capability. From the galvanostatic tests, a capacity of ∼180 mAh g −1 at 1 A g −1 and ∼130 mAh g −1 at 5 A g −1 is attained.